Simple Design Flow Analysis System for Determination of Iron by Spectrophotometric method - Wiwin Setiani; Tri Mulyono; Asnawati Asnawati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
The purpose of this research is to make a series of analyzes using a flow system with a bottle Marriote as pump and spectrophotometric method for determining the content of iron in water samples. Determination of iron by this method used 1,10-fenantrolin complexing or 2,2-bipyridyl. In this method, Fe3+ is reduced to Fe2+ prior complexed with iron to form a specific color and then flowed it through a marriote bottle next to the spectrophotometer detector. The average flow rate of the liquid in the bottle Marriote amounted to 0.037 mL / sec. Limit detection obtained in the batch is 0.00017 ppm and 0.00023 ppm in simple flow systems analysis methods. Sensitivity obtained in the batch method is 0.027 and the simple flow system analysis method is 0.035. Flow rate precision values are expressed Marriote bottle with Kv values <5%. Values accuracy expreced percenting of recovery was 99% in the batch method, whereas the simple flow system analysis method was 98.5%. Results of t-test analysts suggest that iron determination using flow systems analysis (FIA) with the replacement pump bottle Marriote not differ significantly from the results obtained with the batch system. Keywords: batch method, bottle Marriote, Flow Injection Analysis, spectrofotometry